2007
DOI: 10.3108/beej.10.8
|View full text |Cite
|
Sign up to set email alerts
|

The Quantitative Effect of Students Using Podcasts in a First Year Undergraduate Exercise Physiology Module

Abstract: This study reports the quantitative effect of students using podcasts in a 1 st year undergraduate exercise physiology module. From a cohort of 70 students, 50 volunteered and completed the study. Using a pre-post random allocation research design, students were allocated to either a podcast group (PG) or control group (CG) based on a 32-question multiple-choice exam. The PG then listened to six podcasts over six weeks, while the CG were provided with an exact transcript of the podcasts in printed form to ensu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 13 publications
1
35
0
3
Order By: Relevance
“…So, the lecture videos in this instance can primarily be viewed as supplements -rather than replacements -to lectures, although this may be influenced by learning approach, as discussed below. While some previous research has shown positive relationships between lecture capture and performance (Bollmeier, Wenger, & Forinash, 2010;Francom, Ryan & Kariuki, 2011;Harrigan, 1995;McFarlin, 2008;Vajoczki et.al, 2010;), null relationships have also been observed (Abt & Barry, 2007;Brotheron & Abowd, 2004;Joordens et al, 2009;Powell & Barton, 2010;). This study therefore lends support to the finding that at least in certain contexts, provision of lecture capture to students as an additional course resource is positively associated with an increase in performance.…”
Section: Performancementioning
confidence: 90%
See 1 more Smart Citation
“…So, the lecture videos in this instance can primarily be viewed as supplements -rather than replacements -to lectures, although this may be influenced by learning approach, as discussed below. While some previous research has shown positive relationships between lecture capture and performance (Bollmeier, Wenger, & Forinash, 2010;Francom, Ryan & Kariuki, 2011;Harrigan, 1995;McFarlin, 2008;Vajoczki et.al, 2010;), null relationships have also been observed (Abt & Barry, 2007;Brotheron & Abowd, 2004;Joordens et al, 2009;Powell & Barton, 2010;). This study therefore lends support to the finding that at least in certain contexts, provision of lecture capture to students as an additional course resource is positively associated with an increase in performance.…”
Section: Performancementioning
confidence: 90%
“…Here, use of lecture capture for 100 minutes was associated with a grade increase of 15% (Cramer et al, 2007). However, the finding of improved performance with the use of lecture capture is not equivocal, with several studies noting little to no effect on student grades (Abt & Barry, 2007;Brotheron & Abowd, 2004;Powell & Barton, 2010). For example, when lecture capture was used to make more time in class for active learning activities such as discussion and student questions, there was no noted improvement in performance (Jensen, 2011;O'Bannon et al, 2011).…”
Section: Contextmentioning
confidence: 99%
“…A growing number of higher education institutions around the world have incorporated podcasts into both on-campus e-learning modules (Hew, 2009). Despite the growth of podcasting in educational institutions, however, there is little empirical evidence of its tangible effects for improving student grades (Abdous, Facer & Yen, 2012;Abt & Barry, 2007;Kemp et al, 2010;Lazzari and Betella, 2007).…”
Section: Podcasting For Educationmentioning
confidence: 99%
“…By contrast, some researchers found a similar effect on student learning when using other review materials and did not find that the use of podcasts had a significant effect in enhancing student grades (Copley 2007;Lazzari, 2009). Abt and Barry (2007) adopted an experimental research design in the delivery of a physiology course. They found no significant difference between the podcast group and the control group.…”
Section: Effectiveness Of Podcast Learningmentioning
confidence: 99%